82. Changes and Developments in Concepts of Ore Genesis - 1933 to 1967 - John D. Ridge (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Here are summarized 162 papers, published between 1933 and 1967, that deal with various aspects of ore genesis. Emphasis is placed on additions to, or modifications of, ore-formation theory, no matter what type of deposit is discussed. More space is given to papers on the formation of base-metal sulfides solely because more papers are written on this subject. The final conclusion is reached that a chemically and geologically sound theory for the genesis of ore deposits can be built around the concept of concentration of ore e’ements in a magmatically produced ore fluid and around such surface processes as may act to concentrate economically valuable materials from rocks of any origin exposed at the surface.